Meningkatkan Kompetensi Guru Melalui Pelatihan Penulisan Karya Ilmiah di SMAN 1 Kandis Kabupaten Ogan Ilir - Tri Widayatsih; Meilia Rosani; Nurlina Nurlina; Pahlawan Pahlawan; Muhammad Fahmi; Efran Yudia; Anada Luthfillah Qisty F (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
This research aims to improve teacher competence in writing scientific papers through training carried out at SMAN 1 Kandis, Ogan Ilir Regency. In an era of increasingly developing education, the ability to write scientific papers has become an important aspect for developing teacher professionalism. This training is designed to provide teachers with basic understanding and skills in compiling quality scientific work, as well as improving their abilities in conducting research and scientific publications. The method used in this research is a qualitative approach with data collection techniques through observation, interviews and documentation. The results of this training show a significant increase in teachers' understanding and skills in writing scientific papers, as well as a positive impact on their motivation to be more active in research activities and scientific publications. It is hoped that the results of this training can encourage teachers to continue to develop themselves and improve the quality of education at SMAN 1 Kandis.